Revisión bibliográfica de la asignación de personal de enfermería en relación al puesto de trabajo - Dávila Zárate, Jacqueline (2023)
The main objective of this bibliographical research was to determine how the assignment of nursing personnel is carried out in relation to the profile of a job, to achieve this, scientific articles were taken into account with the keywords of personnel assignment, staffing, assignment by competences with an age of 10 years according to the Redalyc, Scielo, Dialnet, Elsevier database. As a result, there were 38 scientific articles that met the inclusion criteria; which presented various models of personnel assignment, each one with its advantages and disadvantages according to the surrounding reality where they had been applied. In conclusion, the literature suggests that proper nursing staff assignment is crucial to ensure quality and safe patient care in hospitals, and that multiple factors and approaches need to be considered to achieve optimal assignment